Project-Based STEAM Learning in Non-Formal Vocational Education: Occupational Korean Proficiency and Delayed Work-Culture Understanding - Lutfi Ariefianto; Rody Putra Sartika; Nurul Faizah (Journal of Nonformal Education, 2026)
Background - The high interest of Indonesian youth in pursuing international career pathways, particularly through the G-to-G placement program to South Korea, poses a major vocational training challenge in the non-formal education sector. Preparing Prospective Migrant Workers (CPMI) requires more than standard linguistic capabilities; it demands deep synchronization with real-world technological environments and the dynamic palli-palli industrial culture. This study is grounded in Law No. 20 of 2003 on the National Education System, which mandates the development of students' optimal skills, independence, and professional competencies. Research Urgency -  Standard language training frameworks in non-formal vocational institutions (LPK) frequently face persistent conventional paradigms, heavily relying on passive rote-learning to pass examinations. This creates a critical skill discrepancy and a link-and-match gap where graduates often experience immediate culture shock upon field deployment due to a lack of interdisciplinary simulation. Therefore, testing innovative instructional frameworks is urgently required to improve vocational readiness. Research Objectives - This study aims to analyze the effect of the integrated STEAM-based learning model on industrial Korean language mastery and work culture retention among young prospective migrant workers. Research Method - This study employs a quantitative approach utilizing a quasi-experimental framework with a Pretest-Posttest Non-Equivalent Control Group Design. The study involved 54 active vocational trainees at LPK Kencana Jember, naturally assigned into Class A as the control group (n = 26) exposed to the conventional method, and Class B as the experimental group (n = 28) treated with the project-based STEAM model. Data gathered through competency tests and retention matrices were statistically processed using Independent Sample t-Tests and ANCOVA via SPSS 26.0. Research Findings - The statistical analysis demonstrated that the project-based STEAM model yields outstandingly superior results. Trainees in the experimental class achieved a significantly faster acceleration in absorbing complex mechanical vocabulary and safety protocols. Furthermore, the ANCOVA results confirmed substantially higher scores in long-term work culture retention (encompassing the palli-palli pace and systemic discipline), proving that the experimental cohort acted far more critically and adaptively when confronting industrial simulations. Research Conclusion - Integrating interdisciplinary STEAM structures effectively bridges the link-and-match gap by shifting traditional supply-oriented language learning into active, demand-driven training. Vocational training centers must structurally enrich their language programs with technological layout mapping and cultural arts role-plays to cultivate job-ready individuals. Research Novelty/Contribution - This research provides one of the first quasi-experimental studies introducing the STEAM framework into the domain of non-formal migrant labor training. It establishes a replicable framework for synchronizing language education with direct industry variables and workplace cultural habits, providing a sustainable model to reduce deployment failure rates.